2000
DOI: 10.1042/cs1000047
|View full text |Cite
|
Sign up to set email alerts
|

Allometric analysis of the association between cardiac dimensions and body size variables in 464 junior athletes

Abstract: Empirically derived relationships between body size variables and cardiac dimensions have not been published previously for a large sample of male and female athletes. This process would inform scaling practice and facilitate intra- and inter-group comparisons of cardiac data. Therefore we investigated the relationships of body mass (BM), height and body surface area (BS) with a range of cardiac dimensions derived by echocardiography in 464 male and female elite junior athletes (age range 14-18 years; sporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Although most cardiac studies rely on linear scaling for correction or normalization, few if any authors check to see whether the normalization process actually removes the correlation of their scaled data with the size variable used for scaling, or indeed, other measures of body size. 3,11,12 Our data indicate that, in all cases, linear scaling actually increases the correlation that the operation seeks to remove and confirms prior observations indicating that allometric rather than linear scaling best corrects for body size. 3,11,12 The superiority of an allometric model is consistent with the observation that physiologic variables in general bear an exponential relationship to body size.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although most cardiac studies rely on linear scaling for correction or normalization, few if any authors check to see whether the normalization process actually removes the correlation of their scaled data with the size variable used for scaling, or indeed, other measures of body size. 3,11,12 Our data indicate that, in all cases, linear scaling actually increases the correlation that the operation seeks to remove and confirms prior observations indicating that allometric rather than linear scaling best corrects for body size. 3,11,12 The superiority of an allometric model is consistent with the observation that physiologic variables in general bear an exponential relationship to body size.…”
Section: Discussionsupporting
confidence: 89%
“…3,11,12 Our data indicate that, in all cases, linear scaling actually increases the correlation that the operation seeks to remove and confirms prior observations indicating that allometric rather than linear scaling best corrects for body size. 3,11,12 The superiority of an allometric model is consistent with the observation that physiologic variables in general bear an exponential relationship to body size. It is also consistent with the theory of geometric similarity, which holds that a linear dimension such as the LAD should be geometrically related to the square root of a twodimensional measure such as BSA and the cube root of a threedimensional measure such as BW.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The use of per ratio standard scaling for anthropometric characteristics has been criticised (Batterham et al 1999). Recent evidence suggests that allometric scaling offers a more meaningful comparison of left ventricular structure (George et al 2001). In the present study a range of body sizes were observed in those athletes presenting with a maximum wall thickness ‡13 mm, suggesting that additional factors, including genetics, may underpin the adaptive response of the left ventricle to a chronic exercise stimulus.…”
Section: Discussionmentioning
confidence: 98%
“…Giraldeau et al presented a collegiate athlete population and demonstrated that sex differences in absolute and ratiometrically scaled LVM were eliminated when allometrically scaled to lean body mass [ 29 ]. Whilst in a cohort of 464 junior athletes, it was found that size independence of LVM was achieved by scaling allometrically to BSA but with a different exponent (b = 1.5) than derived from our data [ 30 ]. This may be related to the wide-age range of our population, reflecting the interaction of both age and athletic adaptation on LVM.…”
Section: Discussionmentioning
confidence: 82%